Sleep links hippocampal propensity for epileptiform activity to its viscerosensory inputs - Levichkina, Ekaterina; Grayden, David B.; Petrou, Steven; Cook, Mark J.; Vidyasagar, Trichur R. (Frontiers in Neuroscience, 2025)
The development of a seizure relies on two factors. One is the existence of an overexcitable neuronal network and the other is a trigger that switches normal activity of that network into a paroxysmal state. While mechanisms of local overexcitation have been the focus of many studies, the process of triggering remains poorly understood. We suggest that, apart from the known exteroceptive sources of reflex epilepsy such as visual, auditory or olfactory signals, there is a range of interoceptive triggers, which are relevant for seizure development in Temporal Lobe Epilepsy (TLE). The hypothesis proposed here aims to explain the prevalence of epileptic activity in sleep and in drowsiness states and to provide a detailed mechanism of seizures triggered by interoceptive signals.